2018
DOI: 10.26434/chemrxiv.5844267
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Versatile AuNP Synthetic Platform for Decoupled Control of Size and Surface Composition

Abstract: While a plethora of protocols exist for the synthesis of sub-10-nm gold nanoparticles (AuNPs), independent control over the size and surface composition remains restricted. This poses a particular challenge for systematic studies of AuNP structure− function relationships and the optimization of crucial design parameters. To this end, we report on a modular two-step approach based on the synthesis of AuNPs in oleylamine (OAm) followed by subsequent functionalization with thiol ligands and mixtures thereof. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Homo-ligand AuNPs stabilized by MUS were prepared via thiol-for-OAm ligand exchange from four batches of differently-sized AuNPs that were initially protected by OAm. 42 As summarized in Tab S1, the core size of the four batches ranged from 2 -7 nm and varying degrees of size dispersity. Two binary mixtures were prepared by mixing MUS-NP1 and MUS-NP4 at weight ratios of 1:1 and 1:5, labeled as MUS-B1 and MUS-B2, respectively (Tab S2).…”
Section: Resultsmentioning
confidence: 99%
“…Homo-ligand AuNPs stabilized by MUS were prepared via thiol-for-OAm ligand exchange from four batches of differently-sized AuNPs that were initially protected by OAm. 42 As summarized in Tab S1, the core size of the four batches ranged from 2 -7 nm and varying degrees of size dispersity. Two binary mixtures were prepared by mixing MUS-NP1 and MUS-NP4 at weight ratios of 1:1 and 1:5, labeled as MUS-B1 and MUS-B2, respectively (Tab S2).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, aliphatic amines including oleylamine have attracted particular interest [41]. In fact, we have recently shown that the use of oleylamine as stabilising agent enables the decoupled control of AuNP size and surface composition, with the former being controlled by the reaction temperature in the initial synthesis and the latter by the subsequent exchange with prescribed thiol ligand mixtures (Figure 3) [42]. Note that this approach offers a decoupled control of size and surface composition by a subsequent thiol-for-oleylamine ligand exchange.…”
Section: Figurementioning
confidence: 99%
“…b) Average size and standard deviation.Note that this approach offers a decoupled control of size and surface composition by a subsequent thiol-for-oleylamine ligand exchange. Reprinted with permission from reference[42] under Creative Commons CC-BY license. Copyright 2018 American Chemical Society.…”
mentioning
confidence: 99%
“…These experimental variables were chosen based on the available literature on this synthetic system. [12][13][14] The levels for each experimental variable in each experimental design are shown in Table 1…”
Section: Experimental Designmentioning
confidence: 99%